eCM 2016
DOI: 10.22203/ecm.v031a04
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of human gingival neural crest-derived stem cells in monolayer and neurosphere cultures

Abstract: Neural crest (NC)-derived stem cells (NCSC) have an exceptionally wide differentiation potential, but their use in regenerative therapy has been hampered by their scarcity in adult tissues and complex isolation protocols. Human oral mucosal gingiva may provide an attractive source of these cells as it contains NC-derived cells, the tissue is easily accessible and wound healing is fast and scarless with very little morbidity. To this end, we first investigated whether NC-derived cells are retained in adult ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 70 publications
1
58
0
Order By: Relevance
“…Our findings led us to hypothesize that heterogeneity in our hDPC cultures could lead to inefficacy in differentiation and that an intermediate population may be required for neural maturation, as shown by observations from the literature on hDPC-neural differentiation. 14,[29][30][31] Together with increasing reports obtaining NCSCs from other dental-derived stem cells, 7,8,32,33 it is suggested that a neural crest or neurogenic population needs to be induced or enriched. In this regard, sphere aggregation has been used to enrich for a neural crest-like phenotype in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings led us to hypothesize that heterogeneity in our hDPC cultures could lead to inefficacy in differentiation and that an intermediate population may be required for neural maturation, as shown by observations from the literature on hDPC-neural differentiation. 14,[29][30][31] Together with increasing reports obtaining NCSCs from other dental-derived stem cells, 7,8,32,33 it is suggested that a neural crest or neurogenic population needs to be induced or enriched. In this regard, sphere aggregation has been used to enrich for a neural crest-like phenotype in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity has been identified as an easily-accessible reservoir of human mesenchymal stem cells (hMSCs) [1,2]. The oral hMSCs were successfully isolated and characterized from a variety of oral tissues, including dental pulp [3], apical papilla [4], exfoliated deciduous teeth [5], dental follicle [6], periodontal ligament [7], and gingiva [8]. Oral stem cells originate from neural crests and represent a transient population of embryonic pluripotent stem cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the tissues of oral cavity have been identified as a rich sources of MSCs. Until now, MSCs from six different type of oral tissues have been reported: dental pulp [Gronthos et al, ], exfoliated deciduous teeth [Miura et al, ], periodontal ligament [Seo et al, ; Trubiani et al, ; Diomede et al, ], apical papilla [Sonoyama et al, ], dental follicle [Morsczeck et al, ], and gingiva [Fournier et al, , ]. A key advantage of these oral tissues‐derived MSCs is that unlike bone marrow tissues collection for the extraction of MSCs, they can be isolated from the oral tissues with restricted morbidity and without additional risks to the donor using minimally invasive procedure.…”
mentioning
confidence: 99%